INOVASI INTERAKTIF MEDIA PEMBELAJARAN INTERAKTIF BERBASIS EDUGAME UNTUK MENINGKATKAN HASIL BELAJAR SAINS SISWA KELAS VI SEKOLAH DASAR - Eliyanti, Ni Kadek; Suastra, I Wayan; Suarni, Ni Ketut (Jurnal Administrasi Pendidikan Indonesia, 2024)
Low motivation and learning outcomes caused by monotonous learning methods cause today's education to be very crucial. This research aims to overcome the low motivation and learning outcomes of students in science learning in grade VI of elementary school by developing Edugame-based interactive learning media. The problem raised in this study is the lack of innovation in learning media that is able to increase student motivation and learning outcomes. This research uses the ADDIE development model which consists of the stages of analysis, design, development, implementation, and evaluation. The research instruments include expert validation questionnaires, teacher practicality questionnaires, and pretest and posttest tests to measure the effectiveness of learning media. The results of media validation with the Gregory formula show a validity rate of 90%, which is categorized as very high. This validity is obtained based on the assessment of material experts and media experts who assess that Edugame has met pedagogic standards, has content that is in accordance with the curriculum, and is supported by  attractive visual and animated elements. The practicality of the media was stated to be very high with a score of 96%, which shows that this media is easy for teachers to use and attractive to students. This practicality is supported by an intuitive interface, interactive features such as multiple-choice questions, drag-and-drop activities, and simulations that make learning more dynamic. In terms of effectiveness, the test results showed a significant increase in student learning outcomes. The average pretest score, which was initially 65.45, increased to 88.73 in the posttest. The N-Gain analysis showed an increase in students' understanding in the high category, which proves that this medium is effective in improving the understanding of science concepts. Thus, the development of Edugame-based interactive learning media has proven to be valid, practical, and effective in increasing student motivation and learning outcomes in science learning